PERILAKU SALES PROMOTION GIRL (SPG) DI KOTA MANADO - Agow, Olvi (Universitas Sam Ratulangi, 2017)
The development of the trade and services sectors in general need worker’s skillmiddle class will but requires carefulness and agility high. Characteristic oflabor this is considered appropriate is female workers. Demand for femaleworkers continue to grow along with the occurrence of growth in the servicessector trade and shopping centers large scale and need workers bulk such assupermarkets and mall of existing in the area of trading center all the way of aBoulevard Manado City.Approach that is used in this research was a qualitative approach which is aprocedure research that yields the data in the form of descriptive writing and ofobservable behavior off the subject itself.Based on the results of research that social behavior that occurs in salespromotion girl (SPG) not only seen during working hours but outside of workinghours is also an influence to the image of a profession and company whorecruited SPG. To be a sales promotion girl, a woman do not need the level of,education the main thing that needed is a form of physical well-proportionedand a beautiful face, in addition in a profession SPG there are severalopportunities which is one reason women to choose this profession, thatopportunity among other: to meet the needs, earn a living, to self existence,increase skills self, can communicate with others, can understand thecharacteristics of another person, it could add insight, can increase networkrelation which is broad, as a springboard for other job, can get businessopportunities, and the employment opportunities in various fields.Keyword: sales, behavior, woman